The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1159/000362557
|View full text |Cite
|
Sign up to set email alerts
|

Central Venous Oxygen Saturation: A Potential New Marker for Circulatory Stress in Haemodialysis Patients?

Abstract: Background/Aims: Haemodialysis causes recurrent haemodynamic stress with subsequent ischaemic end-organ dysfunction. As dialysis prescriptions/schedules can be modified to lessen this circulatory stress, an easily applicable test to allow targeted interventions in vulnerable patients is urgently required. Methods: Intra-dialytic central venous oxygen saturation (ScvO2) and clinical markers (including ultrafiltration, blood pressure) were measured in 18 prevalent haemodialysis patients. Results: Pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 17 publications
4
36
0
Order By: Relevance
“…In a variety of clinical situations ScvO 2 parallels SmvO 2 and is thus regarded as an indirect indicator of CO [19]. Given this physiological significance, ScvO 2 has been proposed as a marker of intradialytic hemodynamic stress in HD patients [20,23]. ScvO 2 has been shown to be lower in patients prone to IDH [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a variety of clinical situations ScvO 2 parallels SmvO 2 and is thus regarded as an indirect indicator of CO [19]. Given this physiological significance, ScvO 2 has been proposed as a marker of intradialytic hemodynamic stress in HD patients [20,23]. ScvO 2 has been shown to be lower in patients prone to IDH [16].…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that rapid excursions of UBBF pose challenges to the CBF autoregulation. While a continuous measurement of upper body oxygen consumption during dialysis is elusive, the continuous measurement of SaO 2 is well established in clinical routine and could provide valuable additional information in future studies [16,18,19,23,[26][27][28][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, changes in central venous oxygen saturation (ScvO 2 ), which can be assessed in patients treated with a central venous catheter, is an integrated parameter influenced by cardiac output, tissue oxygen delivery and oxygen extraction, predominantly of the upper body [35]. While ScvO 2 above 70% is considered optimal, most HD patients already start the dialysis treatment with substantially lower values [35, 36]. ScvO 2 is influenced by ultrafiltration rate [36], whereas the change may be different in patients prone to IDH.…”
Section: Changes In Perfusion Are Important But How Can They Be Measmentioning
confidence: 99%
“…While ScvO 2 above 70% is considered optimal, most HD patients already start the dialysis treatment with substantially lower values [35, 36]. ScvO 2 is influenced by ultrafiltration rate [36], whereas the change may be different in patients prone to IDH. In a study in 11 hypotension-prone and 9 stable HD patients, ScvO 2 dropped by 7.7% ± 1.7 in hypotension prone patients, in contrast to a rise of 1.0 ± 1.3% in the stable group.…”
Section: Changes In Perfusion Are Important But How Can They Be Measmentioning
confidence: 99%
“…More than 20 years ago, it has been demonstrated that SaO 2 decreases during extracorporeal renal replacement therapy [2], and recently, a comparable obser- vation has been made for ScvO 2 [3]. The purpose of this review is to provide an overview about intradialytic SaO 2 and ScvO 2 during HD and its clinical correlates.…”
Section: Introductionmentioning
confidence: 99%